0445 Non-pharmacological Insomnia Therapy is Robust to Co-occurring Pain in Older Adults. (25th May 2022) - Krause, Adam; Ahmadi, Maryam; O'Hora, Kathleen; Hernandez, Beatriz; Lazzeroni, Laura; Zeitzer, Jamie; Friedman, Leah; Posner, Donn; Kushida, Clete; Yesavage, Jerome; Saletin, Jared; Goldstein-Piekarski, Andrea
Abstract: Introduction: Pain worsens insomnia symptoms and increases hyperarousal during sleep. The effectiveness of treatments for improving insomnia symptoms may therefore be affected by co-occurring pain, though this currently remains unknown. Methods: We tested the hypotheses that (1) higher levels of pain will lead to smaller improvements in subjective and objective markers of insomnia following a non-pharmacological insomnia treatment and (2) insomnia treatment will moderate the relationship between pain and markers of insomnia. 114 adults >60 years (age=69.7, SD=6.3, 66% female) with insomnia (Insomnia Severity Index [ISI] score >10, Mean=16.1, SD=4.5) underwent polysomnographic (PSG) recordings before and after completing a 6-session non-pharmacological insomnia treatment regimen. Pain severity (Brief Pain Inventory), insomnia symptoms (ISI), and hyperarousal derived from the PSG (relative α-band power [7.5-12.0Hz] across all sleep stages) were acquired at each time-point. Two-tailed paired t-tests were used to determine the main effects of treatment on insomnia and alpha power. Ranked-correlation tests were used to assess the impact of baseline pain on treatment outcomes, and mixed-effects models were employed to assess whether the relationship between pain and markers of insomnia differed pre- and post-treatment. Results: Non-pharmacological insomnia treatment reduced insomnia symptom severity (t=19.4, p<0.001) but not α-power (t=0.97, p=0.33). Baseline pain severity was not associated with insomnia symptom improvement (ρ=-0.09, p=0.49) nor with changes in α-power (ρ=-0.19, p=0.23). There was no significant pain-by-time interaction in determining insomnia symptom improvement (β=-0.05, t=-0.18, p=0.86), and a trending pain-by-time interaction in determining changes in α-power (β=-0.007, t=-1.8, p = 0.07). Conclusion: These findings suggest that pain is not likely to alter the effectiveness of non-pharmacological treatment for subjective insomnia symptoms, but pain may reduce change in the markers of hyperarousal in older adults with co-occurring pain and insomnia. Support (If Any): National Institute of Mental Health grant 1R01MH101468-01